2002
DOI: 10.2307/3071951
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Stand-Scale Invasion by Hemlock (Tsuga canadensis) at Its Western Range Limit

Abstract: The movement of plant range limits in the past has been clearly documented as a response to changing climate, but the pattern and timing of local invasions that result from these plant migrations are not well understood. Sedimentary evidence from small forest hollows is used here to reconstruct the pattern of stand-scale invasion by eastern hemlock (Tsuga canadensis (L.) Carr.) at its current range limit in Wisconsin. Pollen records from lakes show a slowly increasing regional hemlock population over the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…Studies of Holocene migration dynamics from throughout North America (e.g., Woods and Davis 1989, Jackson and Booth 2002, Parshall 2002, Lyford et al 2003 suggest how such climatic variability can influence the progression of migration events. First, climate modulates the frequency of dispersal events and the distances covered.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Holocene migration dynamics from throughout North America (e.g., Woods and Davis 1989, Jackson and Booth 2002, Parshall 2002, Lyford et al 2003 suggest how such climatic variability can influence the progression of migration events. First, climate modulates the frequency of dispersal events and the distances covered.…”
Section: Discussionmentioning
confidence: 99%
“…Although the post-glacial range dynamics of individual species have been much affected by the different topographies of the two continents (e.g. Parshall, 2002;Hewitt, 2004;Williams et al, 2004), most of the climatic limits under which deciduous trees occur at present in eastern North America and western Eurasia are relatively similar. The absence of drought-sensitive tree species in Europe as compared to North America, however, can hardly be explained only by differences in recent climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In eastern boreal forests, a recent palaeoecological study reconstructing fire history in the Holocene (Cyr et al, 2009) indicated that, despite strong variability in fire intervals, the proportion of old forest in the landscape ranged between 30% and 80% throughout this time period. Likewise, palaeoecological studies suggest low fire frequencies in northern hardwood forests (Foster & Zebryk, 1993;Davis et al, 1998;Parshall, 2002;Parshall & Foster, 2002). Natural fire history reconstruction using dendroecological records has shown that burn rates over the last 300 years were generally higher in the boreal plains region of Alberta (Larsen, 1997) than in the eastern portion of the boreal shield (Bergeron et al, 2001, Figure 1 Location of the study regions where forest bird surveys were conducted in Canadian boreal and northern hardwood forests.…”
Section: Natural Disturbance Regimesmentioning
confidence: 99%